Legal Effects of Fluctuating Exchange Rates - Gold, Joseph (International Monetary Fund, 1990)
This volume, by Joseph Gold, discusses some of the major letgal effects of fluctuating exchange rates in both public international law and national law. The problems and similarities in the solutions are reviewed, and the author recommends further developments in the law.